A TFB-TMS-type lithium-ion battery electrolyte additive, its preparation and application

CN122992173APending Publication Date: 2026-10-27CAMEL GRP XIANGYANG BATTERY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611396920.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]有鉴于此,本申请提供一种TFB-TMS类锂离子电池电解液添加剂及其制备与应用,用于解决如何使锂电池电解液同时具备低腐蚀性、宽工作温区和长循环寿命的问题

Benefits of technology

本专利通过多级纯化与复合稳定体系,显著提升了电解液的本征纯净度和化学稳定性,同时借助缓蚀钝化与成膜技术的协同,有效抑制了高温下集流体的腐蚀及电池产气膨胀,确保长期搁置后仍能恢复优良活性。其复配溶剂与功能添加剂的巧妙组合,既赋予电解液在宽温域下优异的离子传导能力,又能支撑高倍率脉冲放电,满足极端寒冷环境中的瞬时大电流启动需求;而各组分在电极与体相中的空间分工,配合核心化合物贯穿始终的强化作用,使整体性能超越简单加和的局限。整个方案无需新增专用设备,可直接嵌入现有生产线,兼具性能跃升与工艺兼容性,为高安全、长寿命、全天候使用的启停电池提供了切实可行的电解液解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992173A_ABST
    Figure CN122992173A_ABST
Patent Text Reader

Abstract

This invention discloses a TFB-TMS type lithium-ion battery electrolyte additive, its preparation and application. The general structural formula of the TFB-TMS type lithium-ion battery electrolyte additive is (R3Si). n B(N(SO2F)2) m Where n is 1~2, m is 1~2, n+m=3, and R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl; This application uses a quaternary compound system composed of TFB-TMS-type compounds, film-forming additives, corrosion inhibitors and stabilizers in the electrolyte. TFB-TMS-type compounds work synergistically with DMS / HMDS to achieve deep impurity removal, work synergistically with BTA / ADN to inhibit high-temperature corrosion of aluminum foil, and work synergistically with FEC / DFEC to construct a stable SEI film to improve high-temperature cycling and storage performance. At the same time, they also have a viscosity-reducing effect to improve electrochemical activity under low-temperature conditions, so that the lithium battery electrolyte has low corrosion, wide operating temperature range and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery electrolyte technology, and in particular to a TFB-TMS type lithium-ion battery electrolyte additive and its preparation and application. Background Technology

[0002] Lithium-ion batteries are currently widely used in new energy vehicles and large-scale energy storage. The electrolyte directly affects battery performance. Compared to the currently mainstream lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonyl imide (LiFSI) has higher ionic conductivity and better thermal and hydrolytic stability, thus it is considered an important alternative to LiPF6. However, LiFSI alone suffers from aluminum foil corrosion, while LiPF6 alone lacks sufficient thermal and hydrolytic stability. Combining the two leverages the high conductivity and thermal stability of LiFSI while utilizing the ability of LiPF6 to form a stable passivation film on the aluminum foil surface to compensate for the corrosion defects of LiFSI.

[0003] In practical applications, mixed salt electrolyte systems containing LiFSI still have the following problems: First, impurity control is not thorough enough. The Cl in industrial-grade LiFSI... - The content is usually 5-10 ppm, with moisture exceeding 20 ppm and total metal impurities exceeding 10 ppm; LiPF6 also has the problem of excessive moisture and metal impurities. These impurities catalyze the decomposition of lithium salts, damage the SEI film of the negative electrode, and accelerate the electrochemical corrosion of aluminum current collectors, leading to battery capacity decay, gas production and bulging, and in severe cases, internal short circuits. Most existing technologies only control a single impurity, such as only removing water or only controlling a certain anion, lacking a solution to simultaneously treat multiple impurities. Secondly, the problem of aluminum foil corrosion at high temperatures remains prominent. When the proportion of LiFSI is too high, aluminum foil corrosion is obvious, and high-temperature storage and high-temperature cycling performance decreases. When cycling above 45°C, it is difficult to form a stable passivation film on the surface of the aluminum current collector, and FSI... - Will continue to work with Al 3+Complexation and dissolution lead to honeycomb-like corrosion pits on the aluminum foil surface. Therefore, it is necessary to suppress corrosion while maintaining the performance advantages of LiFSI. In existing technologies, the capacity retention rate of pure LiFSI systems or mixed salt systems with an excessively high LiFSI content is usually below 70% after 2000 cycles at 60°C, and the high-temperature long-cycle performance is insufficient to meet the requirements of start-stop batteries. On the other hand, the performance over a wide temperature range is also not ideal. The viscosity of LiFSI-containing electrolytes increases significantly at -20°C, and the ionic conductivity decreases significantly. In high-temperature environments above 60°C, the stability with carbonate solvents decreases significantly, and decomposition and gas production accelerate. Finally, the film formation performance of the negative electrode still needs improvement. The SEI film formed on the graphite negative electrode surface in existing systems is relatively thin, with low cross-linking degree and insufficient mechanical strength. During long-term cycling, the SEI film repeatedly breaks and repairs, and the interfacial impedance continues to rise. Most existing technologies involving LiFSI electrolytes can only improve one aspect of performance, making it difficult to achieve simultaneous improvement in multiple performance aspects.

[0004] Therefore, a technical solution is needed to enable lithium battery electrolytes to simultaneously possess low corrosivity, a wide operating temperature range, and a long cycle life. Summary of the Invention

[0005] In view of this, this application provides a TFB-TMS type lithium-ion battery electrolyte additive and its preparation and application, which is used to solve the problem of how to make lithium battery electrolytes simultaneously have low corrosivity, wide operating temperature range and long cycle life.

[0006] To achieve the above technical objectives, this application adopts the following technical solution: In a first aspect, this application provides a TFB-TMS type lithium-ion battery electrolyte additive with the general structural formula (R3Si). n B(N(SO2F)2) m Where n is 1~2, m is 1~2, n+m=3, and R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl.

[0007] Secondly, this application provides a method for preparing a TFB-TMS type lithium-ion battery electrolyte additive, comprising the following steps: Under an inert atmosphere, boron trichloride and lithium fluorosulfonylimide were reacted with stirring at -10 ~ 0℃ to obtain the boron chloride intermediate ClB(N(SO2F)2)2. Under an inert atmosphere, using boron chloride intermediate and silicon-based lithium reagent R3SiLi as raw materials, the mixture is stirred and reacted at 20~30℃. After vacuum distillation and recrystallization, TFB-TMS type lithium-ion battery electrolyte additive is obtained. Wherein, R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl.

[0008] Preferably, when the target product has the general formula R3SiB(N(SO2F)2)2, the molar ratio of boron trichloride, lithium fluorosulfonylimide, and silicon-based lithium reagent is 1 : (2.0~2.1) : (1.0~1.1); when the target product has the general formula (R3Si)2B(N(SO2F)2), the molar ratio of boron trichloride, lithium fluorosulfonylimide, and silicon-based lithium reagent is 1 : (1.0~1.1) : (2.0~2.1).

[0009] Preferably, the silicon-based lithium reagent R3SiLi includes one or more of trimethylsilane-based lithium, triethylsilane-based lithium, tri(trifluoromethyl)silane-based lithium, trimethylsilane-based lithium, triphenylsilane-based lithium, tri-n-propylsilane-based lithium, and tri(trifluoroethyl)silane-based lithium.

[0010] Thirdly, this application provides a composite additive for lithium-ion battery electrolyte, comprising the following components in parts by weight: 3.0 to 4.0 parts of film-forming additive, 2.0 to 3.0 parts of corrosion-inhibiting and gas-generating additive, 1.0 to 1.5 parts of acid-removing and water-removing stabilizer, and 0.8 to 1.2 parts of the TFB-TMS type lithium-ion battery electrolyte additive as described in claim 1.

[0011] Preferably, the film-forming additive is a compound mixture of fluoroethylene carbonate and difluoroethylene carbonate in a mass ratio of 1.2 to 1.8:1; the corrosion inhibitor and gas-generating additive is a compound mixture of benzotriazole and adiponitrile in a mass ratio of 1.1 to 1.4:1; and the acid and water removal stabilizer is a compound mixture of dimethyl sulfite and hexamethyldisilazane in a mass ratio of 2.2 to 2.8:1.

[0012] Fourthly, this application provides a lithium-ion battery electrolyte comprising the following components in parts by weight: 15-18 parts lithium salt, 75-82 parts non-aqueous mixed organic solvent, and 2-4.5 parts lithium-ion battery electrolyte composite additive as described in claim 5.

[0013] Preferably, the lithium salt is composed of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; wherein, lithium bis(fluorosulfonyl)imide accounts for 11% to 14% of the total mass of the lithium-ion battery electrolyte, and lithium hexafluorophosphate accounts for 3% to 4% of the total mass of the lithium-ion battery electrolyte.

[0014] Preferably, the non-aqueous mixed organic solvent is prepared by compounding ethylene carbonate, diethyl carbonate, methyl ethyl carbonate and ethyl propionate in a mass ratio of 1:1.8~2.2):(2.5~3.5):(0.9~1.2).

[0015] Fifthly, this application provides a method for preparing a lithium-ion battery electrolyte, comprising the following steps: under an inert atmosphere, adding a lithium salt to a non-aqueous mixed organic solvent, stirring to dissolve, then adding a lithium-ion battery electrolyte composite additive dropwise, stirring evenly to obtain a lithium-ion battery electrolyte.

[0016] The beneficial effects of this application are as follows: This patented solution significantly improves the intrinsic purity and chemical stability of the electrolyte through a multi-stage purification and composite stabilization system. Simultaneously, by leveraging the synergy of corrosion inhibition, passivation, and film formation technologies, it effectively suppresses corrosion of the current collector and battery gas expansion at high temperatures, ensuring excellent activity recovery even after long-term storage. The ingenious combination of its compounded solvents and functional additives endows the electrolyte with excellent ion conductivity over a wide temperature range and supports high-rate pulse discharge, meeting the instantaneous high-current start-up requirements in extremely cold environments. Furthermore, the spatial division of labor among the components in the electrode and bulk phases, coupled with the consistent strengthening effect of the core compound, allows the overall performance to transcend the limitations of simple addition. The entire solution requires no additional dedicated equipment and can be directly integrated into existing production lines, offering both performance leaps and process compatibility, providing a practical electrolyte solution for high-safety, long-life, all-weather start-stop batteries. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.

[0018] Figure 1 The NMR spectrum of oxygen-17 for the TFB-TMS type lithium-ion battery electrolyte additive in Example 1 is shown. Figure 2 The carbon-13 nuclear magnetic resonance spectrum of the TFB-TMS type lithium-ion battery electrolyte additive in Example 1; Figure 3 The hydrogen-1 nuclear magnetic resonance spectrum of the TFB-TMS type lithium-ion battery electrolyte additive in Example 1; Detailed Implementation The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0019] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0020] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0021] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character "" in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0022] Unless otherwise explicitly defined and specified herein, all technical and scientific terms used in this application shall have the generally accepted meanings understood by one of ordinary skill in the field of chemical and chemical materials technology (including but not limited to polymer chemistry, inorganic chemistry, organic synthesis, catalysis chemistry, materials processing, and chemical unit operations) based on their professional knowledge and conventional practice. The use of any terminology herein is intended to describe the specific embodiments of this application in the clearest and most accurate manner, so as to fully disclose the technical solution. Such use shall not in any way be construed as a limitation on the scope of the claims, nor does it imply the exclusion of equivalent technical solutions that could be reasonably known by one of skill in the art based on the concept of this application.

[0023] The terms "comprising," "including," "having," "containing," and any grammatical variations or similar expressions used in the specification and claims of this application are all open-ended and non-exhaustive descriptive terms. Their purpose is to explicitly describe the existence of technical features, components, steps, or parts, while explicitly allowing and covering the possibility that other features, components, steps, parts, or any combinations thereof not explicitly listed may exist or be added to the technical solution, as long as such additions do not destroy the integrity and inventiveness of the original technical solution.

[0024] When the terms "embodiments," "some embodiments," or "specific embodiments" are mentioned in the specification, they refer to examples that, in conjunction with the specific parameters, materials, steps, and results described in that section, constitute one or a group of examples for implementing the technical solutions of this application. These embodiments are used for full disclosure and illustrative purposes, not for exhaustive enumeration. Those skilled in the art should understand that, without departing from the overall inventive concept of this application, the various technical features disclosed in different embodiments can be combined, substituted, modified, or deleted to form other implementation methods that are not listed one by one in the specification but also fall within the protection scope of this application.

[0025] Unless otherwise expressly specified and limited, all terms related to chemical process operations, material preparation, processing and analytical testing involved in this application shall be interpreted in the broadest sense based on the conventional understanding of those skilled in the art.

[0026] Regarding performance testing and structural characterization, all testing and characterization methods involved in this application, unless otherwise specified, refer to conventional methods known in the art. Specific testing conditions may be selected and adjusted according to the sample properties and relevant national standards, international standards, or industry-standard methods. Test items may include mechanical properties (such as tensile, bending, and impact strength), thermal properties (such as DSC and TGA analysis), and chemical stability (such as solvent resistance and acid / alkali corrosion resistance). Structural characterization methods may include FT-IR, NMR, XRD, SEM, TEM, and BET. All test results should be understood to be within the allowable range of conventional experimental errors.

[0027] Regarding numerical values ​​and ranges, all parameter ranges expressed in this application in the form of "from a certain value to a certain value" should be understood as explicitly disclosing the endpoints of the range, every specific numerical point between the endpoints, and all sub-ranges formed by any two numerical points within the range. For example, "30℃ to 80℃" discloses 30, 31, 80℃, and sub-ranges such as 30-50℃, 45-70℃, etc. When a numerical value is preceded by "about," "approximately," or similar words, it indicates that the numerical value is allowed to have reasonable errors recognized in the art under the measurement or control conditions, which can generally be understood as the deviation allowed by relevant standards or a normal fluctuation range of ±5% or ±10%.

[0028] This application provides a TFB-TMS type lithium-ion battery electrolyte additive with the general structural formula (R3Si). n B(N(SO2F)2) m Where n is 1~2, m is 1~2, n+m=3, and R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl.

[0029] In the TFB-TMS additives of this application, silicon atoms are directly bonded to boron atoms (R3Si-B<). Part of the σ electron pairs of silicon are delocalized to the empty p orbitals of boron to form back-bonding π bonds, enhancing the Lewis acidity of boron and effectively complexing Cl in the electrolyte. - SO4 2- It also reduces the corrosion of aluminum foil by free anions and metallic impurity ions; at the same time, the fluorosulfonyl imide groups react with Al³⁺. + The formed stable complex constructs a protective passivation layer on the aluminum foil surface, blocking FSI. - The additive mitigates continuous corrosion of the current collector. The alkyl groups on the silicon base provide a hydrophobic environment, inhibiting moisture from approaching the boron center, reducing the risk of HF formation, and further alleviating corrosion. In terms of a wide temperature range, the additive's molecular structure itself has viscosity-reducing properties, improving the overall ion transport efficiency of the electrolyte at low temperatures. Its initial thermal decomposition temperature is ≥320℃, ensuring structural stability under high-temperature conditions. The empty orbitals of boron atoms regulate the Li... + The solvation structure accelerates the desolvation process at low temperatures, reduces interfacial impedance, and thus widens the operating temperature range. Regarding cycle life, this additive covalently bonds with FEC / DFEC, participating in the construction of a highly cross-linked and tough SEI film. Silicon-based components continuously remove trace amounts of water and HF, while boron atoms complex with metallic impurities, forming a dual impurity removal protection with DMS / HMDS, reducing electrolyte decomposition. Fluorosulfonyl imide groups continuously repair the passivation layer on the aluminum foil surface, preventing an increase in contact impedance. Simultaneously, the weak interaction between the additive and lithium salt molecules inhibits the hydrolysis and thermal decomposition of lithium salts, enabling the battery to maintain minimal capacity decay during 3000 high-temperature cycles. These mechanisms work synergistically to achieve breakthroughs in electrolyte performance in terms of low corrosivity, wide operating temperature range, and long cycle life.

[0030] Taking R=methyl, n=1, m=2 as an example, the compound is bis(fluorosulfonylimide)(trimethylsilyl)borane (abbreviated as TFB-TMS), with the molecular formula C3H9BF4N2O8S4Si, a molecular weight of 444.3, and an appearance of a colorless, transparent, viscous liquid. It has a boiling point of 210~212℃, a flash point of 102℃, a solubility of ≥99.8% in non-aqueous organic solvents, a water content of ≤1.5ppm, and an initial thermal decomposition temperature of ≥320℃.

[0031] This application provides a method for preparing a TFB-TMS type lithium-ion battery electrolyte additive, comprising the following steps: Under an inert atmosphere, boron trichloride and lithium fluorosulfonylimide were reacted with stirring at -10 ~ 0℃ to obtain the boron chloride intermediate (ClB(N(SO2F)2)2). Under an inert atmosphere, using boron chloride intermediate and silicon-based lithium reagent R3SiLi as raw materials, the mixture is stirred and reacted at 20~30℃. After vacuum distillation and recrystallization, TFB-TMS type lithium-ion battery electrolyte additive is obtained. Wherein, R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl.

[0032] In some embodiments, when the target product has the general formula R3SiB(N(SO2F)2)2, the molar ratio of boron trichloride, lithium fluorosulfonylimide, and silicon-based lithium reagent is 1 : (2.0~2.1) : (1.0~1.1); when the target product has the general formula (R3Si)2B(N(SO2F)2), the molar ratio of boron trichloride, lithium fluorosulfonylimide, and silicon-based lithium reagent is 1 : (1.0~1.1) : (2.0~2.1).

[0033] In some embodiments, the silicon-based lithium reagent R3SiLi includes one or more of trimethylsilane-based lithium, triethylsilane-based lithium, tri(trifluoromethyl)silane-based lithium, trimethylsilane-based lithium, triphenylsilane-based lithium, tri-n-propylsilane-based lithium, and tri(trifluoroethyl)silane-based lithium.

[0034] Using TFB-TMS type lithium-ion battery electrolyte additives (R3Si) n B(N(SO2F)2) m Taking R = methyl, n = 1, m = 2 as an example, the preparation method is as follows: Raw material preparation: Prepare boron trichloride (BCl3), lithium fluorosulfonylimide (LiN(SO2F)2), and trimethylsilyl lithium ((CH3)3SiLi, usually used in tetrahydrofuran solution) in a molar ratio of 1:2.0~2.1:1.0~1.1; all raw materials are pretreated: boron trichloride is purified by low-temperature distillation (-15~-10℃, vacuum degree 0.08~0.09MPa), lithium fluorosulfonylimide is purified by recrystallization of anhydrous acetonitrile (-5~0℃), and the trimethylsilyl lithium solution is directly prepared using high-purity reagent (concentration 1.0M, ensuring water content ≤1ppm).

[0035] Pretreatment of the reaction vessel: Place the dry four-necked flask under the protection of high-purity argon gas (purity ≥99.999%), put it in a constant temperature water bath, preheat to -10~0℃, and continuously introduce argon gas for 30~40min; Step 1 reaction: Boron trichloride (0.5-0.8 mL / min) is slowly added dropwise at a stirring rate of 200-250 r / min and a temperature of -10-0℃. After the addition is complete, stirring is continued for 15-20 min. The second step of the reaction: keeping the temperature at -10 to 0℃ and the stirring rate constant, slowly add lithium fluorosulfonylimide in batches (1 / 3 of the total amount each time, with an interval of 15 min). After the addition is complete, continue stirring for 1.5 to 2.0 h to generate the intermediate product bis(fluorosulfonylimide)chloroborane (ClB(N(SO2F)2)2) and lithium chloride; The third step of the reaction: keeping the temperature at -10 to 0℃ and the stirring rate constant, slowly add a tetrahydrofuran solution of trimethylsilyl lithium (molar amount the same as boron trichloride, concentration 1.0M) at a dropping rate of 0.6 to 0.9 mL / min. After the addition is complete, raise the temperature to 20 to 25℃ and continue stirring for 1.5 to 2.0 h to generate the target product bis(fluorosulfonylimide)(trimethylsilyl)borane and lithium chloride (LiCl). The LiCl in the reaction solution is removed during subsequent recrystallization and does not require separate treatment. Purification of crude product: Low-boiling substances are removed by vacuum distillation (0.09~0.1MPa, 120~125℃), and LiCl is removed with the mother liquor during recrystallization; the crude product is recrystallized with anhydrous ethanol (solid-liquid ratio 1:4, g / mL, -5~0℃), filtered, and washed 2 to 3 times with anhydrous ethanol. Drying and testing: Vacuum drying (80-85℃, 0.095-0.1MPa, 4-5h) yields a high-purity product (purity ≥99.95%, moisture ≤1.5ppm), which is the TFB-TMS type lithium-ion battery electrolyte additive.

[0036] For other compounds in the general formula (such as R=ethyl, trifluoromethyl, phenyl, n-propyl, trifluoroethyl, or n=2, m=1, etc.), simply replace trimethylsilyl lithium with the corresponding R3SiLi (or the corresponding silyl lithium reagent) and adjust the molar ratio and conditions of the raw materials to obtain the target product. All operations must be carried out in an anhydrous and oxygen-free inert atmosphere.

[0037] This application provides a composite additive for lithium-ion battery electrolyte, comprising the following components in parts by weight: 3.0 to 4.0 parts film-forming additive, 2.0 to 3.0 parts corrosion inhibitor and gas-generating additive, 1.0 to 1.5 parts acid and water removal stabilizer, and 0.8 to 1.2 parts of the TFB-TMS type lithium-ion battery electrolyte additive as described in claim 1.

[0038] In some embodiments, the film-forming additive is a compound mixture of fluoroethylene carbonate and difluoroethylene carbonate in a mass ratio of 1.2 to 1.8:1; the corrosion inhibitor and gas-generating additive is a compound mixture of benzotriazole and adiponitrile in a mass ratio of 1.1 to 1.4:1; and the acid and water removal stabilizer refers to a compound mixture of dimethyl sulfite and hexamethyldisilazane in a mass ratio of 2.2 to 2.8:1.

[0039] This application provides a lithium-ion battery electrolyte comprising the following components in parts by weight: 15-18 parts lithium salt, 75-82 parts non-aqueous mixed organic solvent, and 2-4.5 parts lithium-ion battery electrolyte composite additive as described in claim 5.

[0040] In some embodiments, the lithium salt is composed of lithium bisfluorosulfonylimide and lithium hexafluorophosphate; wherein, lithium bisfluorosulfonylimide accounts for 11% to 14% of the total mass of the lithium-ion battery electrolyte, and lithium hexafluorophosphate accounts for 3% to 4% of the total mass of the lithium-ion battery electrolyte.

[0041] In this embodiment, the impurity content of the lithium salt is controlled as follows: Cl - ≤0.8ppm, SO4 2- ≤4ppm, moisture ≤8ppm, total content of metallic impurities such as sodium, potassium, calcium, and magnesium ≤4ppm.

[0042] In some embodiments, the non-aqueous mixed organic solvent is prepared by compounding ethylene carbonate, diethyl carbonate, methyl ethyl carbonate and ethyl propionate in a mass ratio of 1:1.8~2.2):(2.5~3.5):(0.9~1.2).

[0043] This application provides a method for preparing a lithium-ion battery electrolyte, comprising the following steps: under an inert atmosphere, adding lithium salt to a non-aqueous mixed organic solvent, stirring to dissolve, then adding a lithium-ion battery electrolyte composite additive dropwise, stirring evenly to obtain the lithium-ion battery electrolyte.

[0044] Specifically, the preparation method of lithium-ion battery electrolyte includes the following steps: LiFSI and LiPF6 were purified by recrystallization of anhydrous acetonitrile (crystallization temperature -8~-2℃) until the impurities met the standards. Non-aqueous organic solvents were dehydrated by 4A molecular sieves until the water content was ≤3ppm. Each component of the composite additive was purified to ≤2ppm of water content (TFB-TMS type was prepared and purified according to the above method). The preparation operation is carried out in an inert atmosphere glove box with a dew point ≤ -45℃ and an oxygen content ≤ 1ppm. The non-aqueous organic solvent is added to the reaction vessel according to the ratio. LiFSI and LiPF6 are added in 2 to 3 equal batches with stirring. Stir at 350 to 450 r / min and 22 to 28℃ for 2.5 to 3.5 h until completely dissolved. The film-forming additive, corrosion inhibitor and gas-generating additive, and acid and water removal stabilizer are premixed evenly. Then, TFB-TMS type additives are added and stirred for 0.4 to 0.6 hours. The mixture is then slowly added dropwise to the above solution and stirred for 1.0 to 1.8 hours. After three-stage precision filtration through a 0.22 μm filter membrane, the mixture is sealed and packaged under an inert atmosphere to obtain the lithium-ion battery electrolyte.

[0045] The following specific embodiments further illustrate this solution.

[0046] Example 1 A lithium-ion battery electrolyte comprises the following components by mass percentage: 18% lithium salt, 78% non-aqueous mixed organic solvent, and 4% lithium-ion battery electrolyte composite additive; wherein, based on the total mass of the lithium-ion battery electrolyte, the lithium salt is a mixture of 14% LiFSI and 4% LiPF6, and the lithium salt contains Cl... - =0.6ppm, SO4 2- =3ppm, moisture =7ppm, total metal impurities =3ppm; in the non-aqueous mixed organic solvent, the mass ratio of EC:DEC:EMC:EP is 1:2:3:1.2; in the lithium-ion battery electrolyte composite additive, the mass ratio of film-forming additive, corrosion inhibitor, stabilizer, and TFB-TMS type lithium-ion battery electrolyte additive is 3.5:2.8:1.4:1.3, the film-forming additive is a compound mixture of fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC) at a mass ratio of 1.5:1, the corrosion inhibitor and gas-generating additive is a compound mixture of benzotriazole (BTA) and adiponitrile (ADN) at a mass ratio of 1.2:1, and the acid and water removal stabilizer is a compound mixture of dimethyl sulfite (DMS) and hexamethyldisilazane (HMDS) at a mass ratio of 2.5:1.

[0047] The electrolyte additive for TFB-TMS type lithium-ion batteries is C3H9BF4N2O8S4Si, and its chemical structure is shown in Formula 1: Equation 1; Figure 1 The NMR spectrum of oxygen-17 for the TFB-TMS type lithium-ion battery electrolyte additive in Example 1 is shown. Figure 2 The carbon-13 nuclear magnetic resonance spectrum of the TFB-TMS type lithium-ion battery electrolyte additive in Example 1; Figure 3 The hydrogen-1 nuclear magnetic resonance spectrum of the TFB-TMS type lithium-ion battery electrolyte additive in Example 1; The preparation method of bis(fluorosulfonylimide)(trimethylsilyl)borane (TFB-TMS)C3H9BF4N2O8S4Si, an additive for lithium-ion battery electrolytes, is as follows: Prepare boron trichloride, lithium fluorosulfonylimide, and trimethylsilyl lithium (used as a tetrahydrofuran solution, 1.0 M, water content ≤ 1 ppm) in a molar ratio of 1:2.0:1.0. Purify boron trichloride by low-temperature distillation (-12℃, vacuum 0.085 MPa) and lithium fluorosulfonylimide by recrystallization from anhydrous acetonitrile (-3℃). Place a dry four-necked flask under high-purity argon gas (purity ≥ 99.999%) protection in a constant-temperature water bath to cool to -5℃, continuously purging with argon gas for 35 min. Add boron trichloride slowly dropwise at 0.6 mL / min at a stirring rate of 220 r / min and a temperature of -5℃, continuing stirring for 18 min after the addition is complete. While maintaining a temperature of -5℃ and a constant stirring rate, lithium fluorosulfonylimide was added in batches (1 / 3 of the total amount each time, 15 min apart). After the addition was complete, stirring was continued for 1.8 h to generate the intermediate product bis(fluorosulfonylimide)chloroborane (ClB(N(SO2F)2)2) and lithium chloride. While maintaining a temperature of -5℃ and a constant stirring rate, a tetrahydrofuran solution of trimethylsilyllithium (molar amount the same as boron trichloride, concentration 1.0 M) was slowly added dropwise at 0.8 mL / min. After the addition was complete, the temperature was raised to 22℃ and stirring was continued for 1.8 h to generate the target product bis(fluorosulfonylimide)(trimethylsilyl)borane and lithium chloride. The LiCl in the reaction solution was removed during subsequent recrystallization and did not require separate treatment. Low-boiling substances were removed by vacuum distillation (0.095 MPa, 122 °C), and LiCl was removed with the mother liquor during recrystallization. The crude product was recrystallized with anhydrous ethanol (solid-liquid ratio 1:4, g / mL, -3 °C), filtered, washed twice with anhydrous ethanol, and vacuum dried (82 °C, 0.098 MPa, 4.5 h) to obtain the high-purity product C3H9BF4N2O8S4Si (purity ≥99.95%, moisture ≤1.5 ppm).

[0048] Example 2 A lithium-ion battery electrolyte is identical to that in Example 1, except for the proportions of components and the additives used in the TFB-TMS type lithium-ion battery electrolyte: the lithium salt content is 15 wt%, of which LiFSI is 11 wt% and LiPF6 is 4 wt%; the non-aqueous organic solvent content is 81.5 wt%, of which EC:DEC:EMC:EP is 1:1.8:2.8:1.0; and the composite additive content is 3.5 wt%, of which FEC:DFE... The mass ratio of C is 1.3:1, the mass ratio of BTA:ADN is 1.1:1, the mass ratio of DMS:HMDS is 2.3:1, the mass ratio of film-forming additive, corrosion inhibitor, stabilizer, and TFB-TMS type lithium-ion battery electrolyte additive is 3.0:2.2:1.1:0.9, and the TFB-TMS type lithium-ion battery electrolyte additive is (C2H5)3SiB(N(SO2F)2)2, that is, R is ethyl, n=1, m=2, and its structural formula is shown in Formula 2; Equation 2; The preparation method of TFB-TMS type lithium-ion battery electrolyte additive is the same as that in Example 1, except that the raw materials and conditions are adjusted according to Table 1.

[0049] Example 3 A lithium-ion battery electrolyte, otherwise identical to that of Example 1, except for the proportions of components and the additives used in the TFB-TMS type lithium-ion battery electrolyte: the lithium salt content is 18wt%, of which LiFSI is 14wt% and LiPF6 is 4wt%; the non-aqueous organic solvent content is 78wt%, of which EC:DEC:EMC:EP is 1:2.2:3.2:1.2; the composite additive content is 4wt%, of which FEC:DFEC... The mass ratio of BTA to ADN is 1.7:1, the mass ratio of DMS to HMDS is 2.7:1, and the mass ratio of film-forming additive, corrosion inhibitor, stabilizer, and TFB-TMS type lithium-ion battery electrolyte additive is 3.8:2.9:1.5:1.2. The TFB-TMS type lithium-ion battery electrolyte additive is (CF3)3SiB(N(SO2F)2)2, that is, R is trifluoromethyl, n=1, m=2, and its structural formula is shown in Formula 3. Equation 3; The preparation method of TFB-TMS type lithium-ion battery electrolyte additive is the same as that in Example 1, except that the raw materials and conditions are adjusted according to Table 1.

[0050] Example 4 A lithium-ion battery electrolyte is identical to that in Example 1, except that the total mass percentage of the composite additives in the lithium-ion battery electrolyte is 4.5%, and the mass ratio of film-forming additives, corrosion inhibitors, stabilizers, and TFB-TMS-type lithium-ion battery electrolyte additives is 3.6:2.8:1.4:1.7.

[0051] Example 5 A lithium-ion battery electrolyte is the same as in Example 1, except that the mass ratio of film-forming additive, corrosion inhibitor, stabilizer, and TFB-TMS type lithium-ion battery electrolyte additive is 3.0:2.0:1.0:0.8.

[0052] Example 6 A lithium-ion battery electrolyte is the same as in Example 1, except that the mass ratio of EC:DEC:EMC:EP is 1:1.8:2.5:0.9.

[0053] Example 7 A lithium-ion battery electrolyte is identical to that in Example 1, except for the component proportions and the additives used in the TFB-TMS type lithium-ion battery electrolyte: the lithium salt content is 18 wt%, of which LiFSI is 14 wt% and LiPF6 is 4 wt%; the non-aqueous organic solvent content is 78 wt%; and the composite additive content is 4 wt%, wherein the mass ratio of FEC:DFEC is 1.5:1, the mass ratio of BTA:ADN is 1.2:1, the mass ratio of DMS:HMDS is 2.5:1, and the mass ratio of film-forming additive, corrosion inhibitor, stabilizer, and TFB-TMS type lithium-ion battery electrolyte additive is 3.5:2.8:1.4:1.3. The TFB-TMS type lithium-ion battery electrolyte additive is ((CH3)3Si)2B(N(SO2F) 2) That is, R is methyl, n=2, m=1, and its structural formula is shown in Formula 4; Formula 4; The preparation method of TFB-TMS type lithium-ion battery electrolyte additive is the same as that in Example 1, except that the raw materials and conditions are adjusted according to Table 1.

[0054] Example 8 A lithium-ion battery electrolyte is identical to that in Example 1, except for the proportions of the components and the additives in the TFB-TMS type lithium-ion battery electrolyte: the lithium salt content is 18wt%, of which LiFSI is 14wt% and LiPF6 is 4wt%; the non-aqueous organic solvent content is 78wt%, of which EC:DEC:EMC:EP is 1:2:3:1.2; the composite additive content is 4wt%, and the TFB-TMS type lithium-ion battery electrolyte additive is Ph3SiB(N(SO2F)2)2, i.e., R is phenyl, n=1, m=2, and its structural formula is shown in Formula 5; Equation 5; The preparation method is the same as in Example 1, except that the raw materials and conditions are adjusted according to Table 1.

[0055] Example 9 A lithium-ion battery electrolyte, which is the same as in Example 8 except that the TFB-TMS type lithium-ion battery electrolyte additive is n-Pr3SiB(N(SO2F)2)2, that is, R is n-propyl, n=1, m=2, and its structural formula is shown in Formula 6. Formula 6; The preparation method is the same as in Example 1, except that the raw materials and conditions are adjusted according to Table 1.

[0056] Example 10 A lithium-ion battery electrolyte, which is the same as in Example 8 except that the TFB-TMS type lithium-ion battery electrolyte additive is (CF3CH2)3SiB(N(SO2F)2)2, that is, R is trifluoroethyl, n=1, m=2, and its structural formula is shown in Formula 7. Equation 7; The preparation method is the same as in Example 1, except that the raw materials and conditions are adjusted according to Table 1.

[0057] Table 1. Parameters of TFB-TMS-type lithium-ion battery electrolyte additive preparation methods in different embodiments

[0058] Comparative Example 1 A lithium-ion battery electrolyte, otherwise identical to that in Example 1, except that the lithium salts are unpurified LiFSI and LiPF6 (Cl... - =7ppm, SO4 2- =11ppm, moisture =22ppm, metal impurities =9ppm), lithium salt content is 18wt%, of which LiFSI is 14wt% and LiPF6 is 4wt%; the mass ratio of EC:DEC:EMC:EP is 1:2:3:1.2; and no composite additives are added.

[0059] Comparative Example 2 A lithium-ion battery electrolyte is the same as in Example 1, except that no lithium-ion battery electrolyte composite additives are added.

[0060] Comparative Example 3 A lithium-ion battery electrolyte is the same as in Example 1, except that the lithium-ion battery electrolyte composite additive is replaced with FEC.

[0061] Comparative Example 4 A lithium-ion battery electrolyte is provided, which is otherwise identical to that in Example 1, except that the lithium salt is only LiFSI.

[0062] Comparative Example 5 A lithium-ion battery electrolyte is provided, with all other contents being the same as in Example 1. The difference is that the lithium-ion battery electrolyte composite additive does not include TFB-TMS type lithium-ion battery electrolyte additives, and the total mass percentage of the lithium-ion battery electrolyte composite additive is the same as that of the other three additives.

[0063] Comparative Example 6 A lithium-ion battery electrolyte is the same as in Example 1, except that the mass ratio of film-forming additive, corrosion inhibitor, stabilizer, and TFB-TMS type lithium-ion battery electrolyte additive in the lithium-ion battery electrolyte composite additive is 1:1:1:1.

[0064] Comparative Example 7 A lithium-ion battery electrolyte is provided, which is otherwise identical to that in Example 1, except that the mass ratio of EC:DEC:EMC:EP is 1:1:1:1.

[0065] Comparative Example 8 A lithium-ion battery electrolyte, otherwise identical to Example 1, except that the TFB-TMS type lithium-ion battery electrolyte additive is replaced with an equal mass of a physical mixture of trimethylsilylimidazolium (a silicon compound described in US 2022 / 0231338 A1, CAS No. 18156-74-6) and B(N(SO2F)2)3 (molar ratio 1:1).

[0066] Comparative Example 9 A lithium-ion battery electrolyte, otherwise identical to that in Example 1, except that the TFB-TMS type lithium-ion battery electrolyte additive is replaced with an equal mass of trimethylsilylboronic acid ester ([(CH3)3SiO]3B, where silicon and boron are indirectly connected through oxygen atoms, not directly bonded by Si-B).

[0067] Comparative Example 10 A lithium-ion battery electrolyte is the same as in Example 8, except that the lithium-ion battery electrolyte composite additive is replaced with FEC.

[0068] Comparative Example 11 A lithium-ion battery electrolyte is the same as in Example 8, except that the TFB-TMS type lithium-ion battery electrolyte additive is removed and a ternary additive is used (the total mass percentage remains unchanged), wherein the mass ratio of film-forming additive, corrosion inhibitor and stabilizer is 3.5:2.8:1.4.

[0069] Testing and Evaluation The electrolytes from each embodiment and the comparative example were assembled into 1000mAh lithium iron phosphate / graphite pouch batteries, and performance tests were conducted. The results are shown in Table 2. Table 2 Test Results

[0070] The results above indicate that Comparative Example 4, using pure LiFSI and with other conditions identical to Example 1, exhibited moderate Al foil corrosion, a 2.9% volume expansion rate at 60°C, and a 70% capacity retention rate after 3000 weeks. In contrast, Example 1 (LiFSI 14% + LiPF6 4%) showed no visible corrosion on its Al foil, a 2.0% volume expansion rate, and an 81% capacity retention rate after 3000 weeks. The addition of LiPF6 significantly inhibited aluminum foil corrosion and improved high-temperature storage stability.

[0071] Comparative Example 2 contained no additives at all, while Comparative Example 5 contained ternary additives but no TFB-TMS. Both were inferior to Example 1 in all performance indicators. Comparative Examples 3 and 10 also showed a decline in performance after replacing the quaternary system with a single FEC. This indicates that lithium salt purification and solvent blending alone are insufficient to achieve the goals of wide temperature range and long cycling; TFB-TMS-type additives are indispensable in combination with FEC / DFEC, BTA / ADN, and DMS / HMDS.

[0072] Comparative Examples 8 and 9, which replaced TFB-TMS with physical mixtures of silicon and boron compounds, showed lower performance than Example 1, indicating that the intramolecular synergistic effect resulting from direct silicon-boron bonding cannot be replicated by physical mixing. Furthermore, Examples 8-10 (R = phenyl, n-propyl, trifluoroethyl) showed essentially the same performance as Example 1 (R = methyl), and structural changes within the general formula range did not cause significant performance fluctuations.

[0073] In all embodiments, the indicators of Example 5 are all the lowest values, namely: conductivity at 25℃ 10.0 mS / cm, conductivity at -20℃ 3.3 mS / cm, discharge retention rate at -20℃ 79%, decomposition rate at 60℃ 2.0%, capacity retention rate at 3000 cycles 78%, volume expansion rate at 7 days 2.7%, recovery rate at 28 days 95.0%, minimum pulse voltage at -20℃ / 20C 2.18V, and minimum pulse voltage at -30℃ / 15C 2.12V.

[0074] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A TFB-TMS type lithium-ion battery electrolyte additive, characterized in that, Its general structural formula is (R3Si). n B(N(SO2F)2) m Where n is 1~2, m is 1~2, n+m=3, and R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl.

2. A method for preparing the TFB-TMS type lithium-ion battery electrolyte additive as described in claim 1, characterized in that, Includes the following steps: Under an inert atmosphere, boron trichloride and lithium fluorosulfonylimide were reacted with stirring at -10 ~ 0℃ to obtain the boron chloride intermediate ClB(N(SO2F)2)2. Under an inert atmosphere, using the boron chloride intermediate and silicon-based lithium reagent R3SiLi as raw materials, the mixture is stirred and reacted at 20~30℃. After vacuum distillation and recrystallization, the TFB-TMS lithium-ion battery electrolyte additive is obtained. Wherein, R is one or more of C1~C3 straight-chain alkyl, C1~C2 fluoroalkyl or C1~C2 fluorophenyl.

3. The preparation method according to claim 2, characterized in that, When the target product has the general formula R3SiB(N(SO2F)2)2, the molar ratio of boron trichloride, lithium fluorosulfonylimide, and silicon-based lithium reagent is 1 : (2.0~2.1) : (1.0~1.1); when the target product has the general formula (R3Si)2B(N(SO2F)2), the molar ratio of boron trichloride, lithium fluorosulfonylimide, and silicon-based lithium reagent is 1 : (1.0~1.1) : (2.0~2.1).

4. The preparation method according to claim 2, characterized in that, The silicon-based lithium reagent R3SiLi includes one or more of trimethylsilane-based lithium, triethylsilane-based lithium, tri(trifluoromethyl)silane-based lithium, trimethylsilane-based lithium, triphenylsilane-based lithium, tri-n-propylsilane-based lithium, and tri(trifluoroethyl)silane-based lithium.

5. A composite additive for lithium-ion battery electrolyte, characterized in that, The electrolyte comprises the following components in parts by weight: 3.0 to 4.0 parts film-forming additive, 2.0 to 3.0 parts corrosion inhibitor and gas-generating additive, 1.0 to 1.5 parts acid and water removal stabilizer, and 0.8 to 1.2 parts TFB-TMS lithium-ion battery electrolyte additive as described in claim 1.

6. The lithium-ion battery electrolyte composite additive according to claim 5, characterized in that, The film-forming additive is a compound mixture of fluoroethylene carbonate and difluoroethylene carbonate in a mass ratio of 1.2 to 1.8:1; the corrosion inhibitor and gas-generating additive is a compound mixture of benzotriazole and adiponitrile in a mass ratio of 1.1 to 1.4:1; the acid and water removal stabilizer is a compound mixture of dimethyl sulfite and hexamethyldisilazane in a mass ratio of 2.2 to 2.8:

1.

7. A lithium-ion battery electrolyte, characterized in that, It comprises the following components in parts by weight: 15-18 parts lithium salt, 75-82 parts non-aqueous mixed organic solvent, and 2-4.5 parts lithium-ion battery electrolyte composite additive as described in claim 5.

8. The lithium-ion battery electrolyte according to claim 7, characterized in that, The lithium salt is composed of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; wherein, lithium bis(fluorosulfonyl)imide accounts for 11% to 14% of the total mass of the lithium-ion battery electrolyte, and lithium hexafluorophosphate accounts for 3% to 4% of the total mass of the lithium-ion battery electrolyte.

9. The lithium-ion battery electrolyte according to claim 7, characterized in that, The non-aqueous mixed organic solvent is composed of ethylene carbonate, diethyl carbonate, methyl ethyl carbonate and ethyl propionate in a mass ratio of 1:1.8~2.2):(2.5~3.5):(0.9~1.2).

10. A method for preparing the lithium-ion battery electrolyte as described in claim 7, characterized in that, Includes the following steps: Under an inert atmosphere, lithium salt is added to a non-aqueous mixed organic solvent and stirred to dissolve. Then, lithium-ion battery electrolyte composite additives are added dropwise and stirred evenly to obtain the lithium-ion battery electrolyte.

Citation Information

Patent Citations

  • Nonaqueous Electrolytic Solution

    US20220231338A1